Chapter Introduction An Ecology of Embodied VulnerAbility- Literary and Filmic Representations across the Globe - Gámez Fernández, Cristina María (Taylor & Francis, 2024)
Introduction: Aiming to provide a theoretical introduction that further informs the analyses conducted in subsequent chapters, this chapter will review the synergies operating among the different conceptualizations of vulnerability and various well-established theories that explore the materiality of the body and its affects from multifold viewpoints. Divided into three sections, the first explores some of the most salient critical proposals related to vulnerability and the body by manifesting the semantic multiplicity that applies to these terms. This is a necessary step to sketch an operational frame in which to contextualize the literary and filmic research endeavor of the collection. The second section ponders on the ethical and aesthetic features that make possible the integration of complementary and competing configurations of vulnerability in the production of literary texts and audiovisual productions and explores its salient elements that place literature and film as a privileged sites of expansion, critical reflection, and challenge of vulnerability both as a universal condition as well as a particular and specific manifestation in historical, geopolitical, social, and cultural and natural dimensions. Finally, the chapter closes with a brief description of the twelve essays collected in the volume by discussing their organizational logics and their distinct contribution to it.